CIVIL NATION IN THE CONTEXT OF NATIONAL CONSCIOUSNESS: THE REPUBLIC OF UZBEKISTAN - AKHMEDOV, Ghelman (CENTRAL ASIA AND THE CAUCASUS, 2009)
National communities create corresponding national consciousnesses, which meansthat the number of nations living on Earth corresponds to the number of national conscious-nesses. Every nation has national consciousness, which means that it thinks. As a thinking entity it determines the way its national features are developed in all, including spiritual, spheres. It produces thoughts, regulates their production, and dis-tributes them. The fact that national consciousness has its own components is its specific feature; they reflect the national conditions of life, national interests, and national relations and, therefore, determine the content of national consciousness. It serves as the core of consciousness that keeps alive the faith that one’s nation is capable of in-dependent national creativity and of historically conditioned interpretation of its national and state sovereignty. So far most of the world’s nationalities have no national statehood of their own, which means that for a long time to come ethnic awareness will determine political dynamics. Elements of alien consciousnesses invariably affect (negatively or positively) all functioning national consciousnesses. The most active among them are of universal significance. They can be described as elements related to the need to develop civil societies, the structure of which exceeds the limits of ethnic identity and is kept together by shared civil interests.